(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Field trials and laboratory bioassay were used to evaluate the effects of transgenic com, that produces the CryIAb toxin of Bacillus thuringiensis, on non the target species Lydella thompsoni Herting, parasitoid of Ostrinia nubilalis Hb .. In 1998 and 1999 the larvae of O. nubilalis were collected from Bt com and non Bt-com at 9 geographical sites. Considering the tota! larva amount, the European com borer (ECB) from transgenic com showed lower parasitism levels in terms of both percentage and absolute parasitoid number. In fact the statistica! analysis demonstrates that, over the two years, there was a difference in parasitism rate by L. thompsoni in Bt maize versus the near isogenic non-Bt maize. However four localities had higher parasitism percentages for Bt com larvae. It was also shown that there was a significant variation in the parasitism rate in the fields and field locations. There were no significant differences in parasitism in the two years, and none of the interactions were significant. The biology of L. thompsoni parasitizing ECB larvae from isogenic and transgenic corn was investigated. The parasites emerging from borers reared on the two maize hybrids showed no significant difference in lifespan or adult longevity. However as corn borer populations decline in Bt corn and this study -report a decline as well of the number of parasitoid, refuge areas, may moderate these indirect effects and they should considered also for conserving natural enemie s.